La exposición de los resultados financieros como mecanismo de valor en la gestión empresarial en una empresa reportante (2024)
This study investigates the exposure of financial and non-financial results in the company Colombina, listed in the stock exchange, using a descriptive methodology of the information requirements in the stock market. It highlights the need for investors to have complete information for decision making.